2020
DOI: 10.21608/ejhc.2020.176793
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Educational Program on Pregnant Knowledge and Practice Regarding How to Continue Breast Feeding after Returning to Work

Abstract: Background: An important factor influencing duration of breastfeeding is mother's employment status. Aim: To investigate the effect of educational program on pregnant knowledge and practice regarding how to continue breast feeding after returning to work. Design: A quasi-experimental design was utilized. Setting: The study was conducted at Outpatient Clinic and High risk Units of special Hospital at Beni-Suef University. Sample: A convenience sample of all available pregnant working women (300 women) from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…One-third and more than one-third of the remaining percentage of the study and control group respectively have their knowledge from internet resources, followed by low percent (from their mothers, and the minority take their knowledge from nurses. This finding is matching with Ahmed et al [16] confirmed that women relied primarily on their families and the media for updates and knowledge. And in the same line with Mohamed & Hassan [12] , mentioned friends and relatives were the main source of information about dental health care, as mentioned by the studied sample.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…One-third and more than one-third of the remaining percentage of the study and control group respectively have their knowledge from internet resources, followed by low percent (from their mothers, and the minority take their knowledge from nurses. This finding is matching with Ahmed et al [16] confirmed that women relied primarily on their families and the media for updates and knowledge. And in the same line with Mohamed & Hassan [12] , mentioned friends and relatives were the main source of information about dental health care, as mentioned by the studied sample.…”
Section: Discussionsupporting
confidence: 88%
“…This result is in accordance with Rezaie et al [15] , conducted in Iran, indicated that the overall health practices of the ~ 103 ~ women in the intervention group was significantly higher after the intervention than that of the women in the control group, suggesting that self-care counseling has a positive effect on health practices and its subdomains, particularly attitudes towards motherhood and pregnancy. And in the same line with Ahmed et al [16] , in Beni-Suef University, pregnant working women showed considerable improvement in their testing behavior between pre-and post-test, according to the study. This agreement might be due to one of the most significant predictors was grade of education for the self-care practice among antenatal mothers and explained that antenatal mothers with a good education were associated with a higher-level score of their practice and enhanced their understanding and receiving of information about cervical cerclage and followed the instruction in the handout booklet.…”
Section: Discussionsupporting
confidence: 82%